Orphological variations of Procoxae and Metacoxae Hypothenemus hampei FERRARI, 1867 (COLEOPTERA: CURCULIONIDAE: SCOLYTINAE) on three species of coffee berries in Sumatra, Indonesia - Aida Fitriani Sitompul,; Dahelmi,; Dewi Imelda Roesma, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Coffee Berry Borer (Hypothenemus hampei Ferarri, 1867) is a serious pest of coffee and has a wide distribution worldwide, including in Sumatra, Indonesia. During our investigation on the coffee plantations of Sumatra, we found that H. hampei infested three different species of coffee (Coffea arabica, C. cenophora, and C. liberica). This study aimed to describe the morphological variations of H. hampei that infested the three coffee species. The morphological variations recorded in H. hampei infested on the three species of coffee were: the number of denticles on the fore legs (procoxae) and hind legs (metacoxae). The result showed that the number of denticles on procoxae and metacoxae, respectively: are six and four (in C. arabica), seven and four (in C. cenophora), and seven and three (in C. liberica). The highest result of the hardness and thickness test of coffee was in C. liberica (236,81 N/Cm2; 2.33 mm).